Iron Status Alterations in Osteoporotic Pre and Postmenopausal Women: Perubahan Status Zat Besi pada Wanita Pra dan Pasca Menopause dengan Osteoporosis - Mustafa Abd Almajeed Hussein; Nawal Khalil Ibrahim; Saja Hasan Saleem (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Osteoporosis is a major skeletal disorder associated with fractures, disability, and increased mortality among women. Specific Background: Alterations in bone metabolism may influence hematological parameters and iron status, particularly during the menopausal transition. Knowledge Gap: Limited data are available regarding the association between blood variables and iron status in pre- and post-menopausal women with osteoporosis in Basrah. Aims: This study aimed to evaluate blood parameters and iron status indicators among pre- and post-menopausal women suffering from osteoporosis. Results: Ninety-seven women aged 40–60 years were assessed using DEXA and laboratory analysis. Osteoporotic women showed significant decreases in hemoglobin, packed cell volume, and serum iron, accompanied by a significant increase in serum ferritin. Red and white blood cell counts and total iron-binding capacity showed no significant changes compared with healthy controls. These findings were consistent in both pre- and post-menopausal groups. Novelty: The study provides regional evidence linking iron status disturbances with osteoporosis among menopausal women in Basrah. Implications: Monitoring iron-related blood parameters may support clinical evaluation of osteoporosis in pre- and post-menopausal women. Keywords: Osteoporosis, Iron Status, Hemoglobin, Ferriti, Menopausal Women Key Findings Highlights: Reduced hemoglobin and packed cell volume were observed in osteoporotic women. Serum iron levels declined while ferritin levels increased in affected groups. Cellular blood counts remained stable despite altered iron profiles.